Singlet spin order in spin pairs coupled via non-bonded interactions - Pileio, Giuseppe; Yamano, Dolnapa; Eccles, Craig D.; Tizzard, Graham J.; Thompson, Sam (Frontiers in Chemistry, 2025)
Fluorine spin pairs that are constrained in spatial proximity show large scalar spin-spin couplings, despite the atoms being separated by several bonds. This is due to a non-bonded atomic interaction related to partial overlapping of fluorine p-orbitals. In this paper we exploit this phenomenon to create long-lived singlet spin order on the fluorine spin pair. This form of order, which, in this example molecule, is more than an order of magnitude longer than longitudinal order, has the potential to be useful in magnetic resonance imaging and molecular tracing experiments, because of the lack of endogenous fluorine in the human body and the high sensitivity achievable in 19F NMR.